Pengaruh Media Sosial, Influencer Marketing, Dan Flash Sale Terhadap Keputusan Pembelian Brand Eiger ( Studi Kasus Pada Konsumen Brand Eiger Di Kota Malang) - Rahananda, Salma Regita; Asiyah, Siti; Rahmawati, Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the influence of social media, influencer marketing, and flash sales on purchasing decisions of the Eiger brand in Malang City. The background of this research is based on the rapid growth of digital marketing, the rising use of social media, and the trend of using influencers and flash sales as key strategies in promoting local brands. This research employed a quantitative approach using purposive sampling, with data collected through questionnaires from 125 respondents who are consumers of the Eiger brand in Malang. Data were analyzed using multiple linear regression. The results show that social media, influencer marketing, and flash sales simultaneously have a significant effect on purchasing decisions. Partially, social media and influencer marketing have a significant effect, while flash sales show a more moderate influence. The study concludes that the combination of these three digital marketing strategies can be an effective approach in enhancing consumer purchase decisions, especially in the urban youth market. Keywords: Social Media, Influencer Marketing, Flash Sale, Purchase Decision, Eiger Brand